Melatonin Maintains Anabolic-Catabolic Equilibrium and Regulates Circadian Rhythm During Osteoarthritis Development in Animal Models: A Systematic Review and Meta-analysis - Sumsuzzman, Dewan Md.; Choi, Jeonghyun; Khan, Zeeshan Ahmad; Kamenos, George; Hong, Yonggeun (Frontiers in Pharmacology, 2021)
Background: The driving force behind osteoarthritis (OA) pathogenesis is an anabolic-catabolic (a/c) imbalance. Melatonin (MT) is a key player in maintaining a/c stability and mitigates OA pathogenesis, but mechanisms underlying its effects remain poorly understood. Objectives: We performed a systematic review analyzing the experimental data that support the clinical applicability of MT in the treatment of OA pathogenesis, placing particular emphasis on the regulation of circadian rhythms and anabolic-catabolic balance. Methods: Major electronic databases and grey literature were used to identify related original articles. Methodological quality of all selected studies was evaluated using the SYRCLE risk of bias tool. Pooled mean differences (MDs)/standardized mean differences (SMDs) with 95% confidence intervals (CIs) were calculated to estimate the effect size. Results: Eleven trials were included in this systematic review. Compared with the control group, MT significantly decreased the levels of interleukin-1β (IL-1β; SMD = −5.45; 95% CI [−6.78, −4.12]; p < 0.00001, and histological grading scale (SMD = −3.46; 95% CI, [−5.24, −1.68]; p < 0.0001). MT significantly increased the transforming growth factor-β1 (TGF-β1; SMD = 1.17; 95% CI [0.31, 2.03]; p < 0.0007). Furthermore, core circadian clock genes Per2 and Cry1 mRNA levels were regulated by MT treatment in OA progression. Conclusion: MT may maintain anabolic-catabolic balance and regulate circadian rhythms during OA development. MT could be used in as adjunct with other interventions to manage pain and OA severity.